Environmental Contribution of Community Forests For Food Production With Agroforestry Patterns - Anang Susanto; Marti Winarni; Maher Nasser Abdullah; Dana Briggs (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Application of agroforestry systems in Indonesia through production forest programs in Java. Impact on the use of the production forest land. This research aims to present a variety of positive and negative effects on the use of production forest land for agricultural production in agroforestry systems. Agroforestry activities certainly have both positive and negative impacts on the primary production of forestry, the environment, and the income of communities living around the forest. Positive effects include: Increasing land productivity/value-added, accelerating the growth of primary production, providing short and medium-term income, reducing the risk of forest fires ,Opening up forest fires.Employment opportunities, Improving the environment and biodiversity, reducing global warming, producing dry leaf mulch, and increasing people's income. The negative impact of agroforestry patterns is the tendency of agroforestry farmers to extend the farming time by disrupting primary production